2007
DOI: 10.1016/j.rmed.2007.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of nebulized human recombinant DNase1 in two siblings with primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is characterized by ultra-structural defects of the cilia. In this report, we describe the long-term use of nebulized dornase alfa in two siblings with PCD. This is the first report of long-term use of dornase alfa in PCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…150 Several case reports of DNase in PCD suggest possible benefit when used for both short and long-term periods. [151][152][153] Larger, prospective clinical studies of DNase in children and young adults with PCD are required before the potential negative effects of this medication can be dismissed.…”
Section: Therapies To Consider On a Case By Case Basis In Pcdmentioning
confidence: 99%
“…150 Several case reports of DNase in PCD suggest possible benefit when used for both short and long-term periods. [151][152][153] Larger, prospective clinical studies of DNase in children and young adults with PCD are required before the potential negative effects of this medication can be dismissed.…”
Section: Therapies To Consider On a Case By Case Basis In Pcdmentioning
confidence: 99%
“…Neutrophilic airway inflammation has been reported in PCD (123). Until now, few PCD studies have showed significant clinical benefits of a trial with inhaled DNase (124126). At present, rhDNase is not recommended in PCD, and larger studies are needed to confirm its efficacy in PCD.…”
Section: Current and Future Treatment Strategiesmentioning
confidence: 99%
“…Recombinant human DNase I cleaves extracellular DNA, decreasing the DNA concentration, and thereby decreasing sputum viscosity. There are several case reports noting improvement in pulmonary symptoms in PCD patients with both intermittent 61 and chronic use 62, 63 . Although PCD airway secretions contain elevated DNA concentrations 55 , it is not to the same degree as CF.…”
Section: Disease Managementmentioning
confidence: 99%